The cost of equity for private firms - Abudy, Menachem; Benninga, Simon; Shust, Efrat (Journal of Corporate Finance, 2016)
The paper presents a method for calculating the cost of equity capital for the non-marketable securities of private firms and its difference from the cost of equity capital of an all else equal public firm (the private firm premium). The method is based on a theoretical framework that assumes the investor is undiversified due to her holdings in non-marketable securities. We implement the method for both unlevered and levered firms, and also consider the effect of taxes. The findings indicate that the private firm premium increases with the firm's asset risk, its leverage ratio, and the non-diversification of the private firm's owner, while taxes are negatively related to the private firm premium.